1998
DOI: 10.1002/ana.410430209
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable neuronal subsets in Alzheimer's and Pick's disease are distinguished by their τ isoform distribution and phosphorylation

Abstract: Aggregated tau proteins constitute the basic matrix of neuronal inclusions specific to numerous neurodegenerative disorders. Monodimensional and two-dimensional Western blot analyses performed on cortical brain homogenates allowed discrimination between disease-specific tau protein profiles. These observations raised the issue of the physiopathological significance of such specificities. Alzheimer's disease (AD) pathological tau proteins (PTPs) (tau 74, 69, 64, 55) were compared with those of Pick's disease (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
2
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(145 citation statements)
references
References 42 publications
13
127
2
3
Order By: Relevance
“…In myotonic dystrophy, 3R aggregation reflects primarily an abnormal MAPT expression pattern favoring exclusion of exons 2, 3, and 10 (62). In contrast, 3R aggregation in Pick disease occurs in certain cell populations (63), perhaps reflecting selective vulnerability of cells expressing primarily 3R Tau (e.g. neural precursor cells (64)).…”
Section: Discussionmentioning
confidence: 99%
“…In myotonic dystrophy, 3R aggregation reflects primarily an abnormal MAPT expression pattern favoring exclusion of exons 2, 3, and 10 (62). In contrast, 3R aggregation in Pick disease occurs in certain cell populations (63), perhaps reflecting selective vulnerability of cells expressing primarily 3R Tau (e.g. neural precursor cells (64)).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of intronic mutations to induce dominant familial tauopathy syndromes by creating an imbalance between three and four-repeat tau isoforms [70][71][72] also demonstrated that tau toxicity is dependent on an extremely subtle interplay between the parameters associated with MT:tau binding, tau:tau binding, and tau hyperphosphorylation.…”
Section: Tau -The Amyloid Cascade Hypothesis Is Incompletementioning
confidence: 99%
“…Cependant, Les corps de Pick sont localisés principalement dans les couches II et VI de l'isocortex et les neurones granulaires du gyrus denté. Ces neurones ne contiennent pas les isoformes 10+ de protéines tau [16]. Or, seules les isoformes de protéines tau hyperphosphorylées dépour-vues de la séquence codée par l'exon 10 (3R) présentent un tel profil électrophorétique [15,17].…”
Section: Les Protéines Tau Normalesunclassified
“…Il est donc clair que des isoformes ne comportant pas cette séquence s'agrègent au sein des corps de Pick ( Figure 5). De plus, certains sites (KXGS), tels que les résidus Ser262 et 356, ne sont pas phosphorylés, suggérant l'absence ou l'inactivation des kinases impliquées dans cette phosphorylation, ou encore un problème d'accessibilité à ces sites [15,16]. Le profil électrophorétique des protéines tau permet donc de différencier certaines maladies neurodégéné-ratives.…”
Section: Les Protéines Tau Normalesunclassified